2013
DOI: 10.1515/jpem-2013-0135
|View full text |Cite
|
Sign up to set email alerts
|

Fasting glucagon-like peptide-1 in patients with overt hyperthyroidism and euthyroid congenital hypothyroidism

Abstract: Fasting GLP-1 levels in the peripheral circulation were significantly increased in overt hyperthyroidism, however, they were no different in euthyroid congenital hypothyroidism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…The hypothyroid patients had received regular treatment for thyroid dysfunction and were diagnosed based on serum thyrotropin (TSH), free thyroxine (FT4), and free triiodothyronine (FT3) levels at birth, as previously described (1) . Daily doses of 25 -100 μ g L-thyroxine were administered.…”
Section: Patient Recruitment and Exclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…The hypothyroid patients had received regular treatment for thyroid dysfunction and were diagnosed based on serum thyrotropin (TSH), free thyroxine (FT4), and free triiodothyronine (FT3) levels at birth, as previously described (1) . Daily doses of 25 -100 μ g L-thyroxine were administered.…”
Section: Patient Recruitment and Exclusion Criteriamentioning
confidence: 99%
“…Although standard L-thyroxine supplementation in patients with CH is a safe treatment, it often leads to disrupted autoregulation due to fluctuations in circulating thyroid hormones. In our medical center, most of the patients with CH were kept euthyroid in the regular follow-up (1) . However, to perform our work thoroughly and well, it is necessary to pay attention to inflammatory and oxidative status, as they can provoke significant complications.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, baseline GLP-1 levels did not differ significantly between patients with hyperthyroidism and healthy controls. In contrast, Cheng et al 16 reported higher fasting GLP-1 levels in newly diagnosed children with untreated hyperthyroidism. Although the reason for our contradictory findings is not clear, differences in patient populations in terms of age, sex, and degree of hyperthyroidism, together with variations in intestinal discharge times, might play a part.…”
Section: Discussionmentioning
confidence: 87%
“…However, GLP-1 response to an oral glucose load was not evaluated. 16 In our study, both baseline levels and responses of GLP-1 and GIP to an oral glucose loading dose were evaluated in patients with hyperthyroidism. Additionally, to our knowledge, it is the first study that investigates the changes in incretin levels induced by establishment of euthyroid state with antithyroid medications in patients who previously had hyperthyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…In fasting rats, PYY 3–36 at a dose of 3 or 30 μg/kg bodyweight elicited a significant rise in serum TSH observed 15 min after PYY 3–36 injection . It has also been reported that the fasting GLP‐1 level in pediatric human patients with overt hyperthyroidism was significantly increased . In contrast, Tateishi et al .…”
Section: Discussionmentioning
confidence: 96%